Deterring effects of 8-45 kHz tone pulses on harbour seals (Phoca vitulina) in a large pool: - Kastelein, R.A.; Heul, S. van der; Terhune, J.M.; Verboom, W.C.; Triesscheijn, R.J.V. (2006)
The marine aquaculture industry suffers losses due to pinniped attacks which damage net enclosures and fish stocks. Acoustic harassment devices (AHDs) emit loud sounds which are intended to deter pinnipeds from approaching aquaculture enclosures. At present, many AHDs emit sounds in the 8-20 kHz frequency range. It is not known whether sounds of higher frequencies have a deterrent effect on seals. Therefore five captive harbour seals (Phoca vitulina) were subjected to four series of tone pulses together spanning a broad frequency range (8, 16, 32 and 45 kHz). Pulse duration was 250 ms and pulse interval was 5 s. Each of the four sounds was made deterrent by increasing the amplitude. The seals reacted by swimming away from the sounds. The displacement effect of each sound was judged by comparing the animals' surface positions, and number of surfacings, during ten 45 min baseline periods with ten 45 min test periods per frequency (one frequency per day in rotation, 40 sessions in total). The seals were displaced by all four frequencies throughout the 40 trial days. The seals came to the surface more often when the test tones were produced than in the baseline periods. The initial displacement distances did not change over the 40 test days. This suggests that operating AHDs for only short periods will be more effective and less likely to result in habituation by the seals than operating them continuously. The discomfort threshold sound pressure level (SPL) was established for each of the four pulse frequencies. The acoustic discomfort threshold SPL is defined as the boundary SPL between the area that the animals generally occupied during the transmission of the sounds and the area that they generally did not enter during sound transmission. The discomfort threshold SPL may depend on the context. © 2006 Elsevier Ltd. All rights reserved.